If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6r = 3r + 1 Reorder the terms: 12 + -6r = 1 + 3r Solving 12 + -6r = 1 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 12 + -6r + -3r = 1 + 3r + -3r Combine like terms: -6r + -3r = -9r 12 + -9r = 1 + 3r + -3r Combine like terms: 3r + -3r = 0 12 + -9r = 1 + 0 12 + -9r = 1 Add '-12' to each side of the equation. 12 + -12 + -9r = 1 + -12 Combine like terms: 12 + -12 = 0 0 + -9r = 1 + -12 -9r = 1 + -12 Combine like terms: 1 + -12 = -11 -9r = -11 Divide each side by '-9'. r = 1.222222222 Simplifying r = 1.222222222
| (1/4h | | 4n+4=36whatsn | | 24xy-8y+18x-6=0 | | T/-8=-7 | | 6x+1.5=0x+2 | | 24+ln(x)=19 | | -1x+5=40 | | 10/4=4K/9 | | -38-12x=-8x+16 | | y^2+14y-36=0 | | 24+lnx=19 | | 5x=-3X+26 | | -15=6p+15+-10p | | (x-3)(x^2-29)=0 | | w(t)=250-150e-0.4t | | h(t)=-16t^2+64t+136 | | 2/7y-1/7=3/14 | | 3x-(-1+3x)=1 | | 5/4c-4=-14 | | -85-12x=-89-6x | | kx^2-14x+49=0 | | 2y+3y+13=23 | | -16=-6-5z | | h(t)=-16t^2+192t+90 | | 27+35+23=180 | | 2z-13=27 | | -40=-5pm | | 23-3w=80 | | 240x^3+540x^2-2160x=0 | | 8x-22=3(3x+21)-x | | 1492=75 | | -7x-66=-2x+54 |